Micromechanical simulation of porous asphalt mixture compaction using discrete element method (DEM). (27th September 2021) - Al Khateeb, Loay; Anupam, Kumar; Erkens, Sandra; Scarpas, Tom
Highlights: Simulating the micromechanical behavior of asphalt mixes during compaction using DEM. Representing the micromechanical interactions using a viscoelastic contact model. The influence of temperature on the compaction process and compactability. Analyzing the internal structure and air-void distribution during the compaction. Abstract: The paper aims to simulate the micromechanical behavior of asphalt mixtures during the compaction process using the Discrete Element Method (DEM). The interactions between the components of a Porous Asphalt (PA) mixture were represented using an Elastic Viscoelastic Contact Model (EVCM), which is a user-defined model implemented in EDEM software, developed based on linear elastic and Burger's viscoelastic constitutive equations. The macroscale parameters of asphalt mortar were characterized using the nonlinear regression analysis of master curves obtained from Dynamic Shear Rheometer (DSR) tests. The verification process of EVCM successfully indicated that the computations trends fall within the range of expected values for the typical asphalt mixture material. Further, a Superpave Gyratory Compaction (SGC) test was carried out and the obtained sample was scanned using X-ray Computed Tomography (X-ray CT) to capture the air void distributions. The DEM was utilized where digital samples were established to simulate the overall process of laboratory and field compaction. The simulation results showed that the model provided a comparable prediction of responses and demonstrated the capability of SGC to fabricate a representative sample. The influence of temperature on the asphalt compaction process was explored and the results implied that temperature decreasing adversely affects the compactability and dramatically increases the demanded compaction efforts which are consistent with the law of viscoelasticity. On the contrary, when the temperature is high, the asphalt binder becomes too fluid and roller loads will simply displace, or "shove" the mat rather than compact it. Tracking the change in the air voids proportion indicates that the motion of aggregates is rather compound. The aggregates flowed vertically downwards in line with the compacting orientation while moved horizontally outwards away from the center. All in all, the findings confirm that the concept is technically practicable, affording the model great potential to help researchers understand the microstructural phases of asphalt mixture during the compaction.